1999
DOI: 10.1093/glycob/9.10.1061
|View full text |Cite
|
Sign up to set email alerts
|

High-level expression of the Neisseria meningitidis lgtA gene in Escherichia coli and characterization of the encoded N-acetylglucosaminyltransferase as a useful catalyst in the synthesis of GlcNAc 1->3Gal and GalNAc 1->3Gal linkages

Abstract: We have expressed the Neisseria meningitidis lgtA gene at a high level in Escherichia coli. The encoded beta-N-acetylglucosaminyltransferase, referred to as LgtA, which in the bacterium is involved in the synthesis of the lacto-N-neo-tetraose structural element of the bacterial lipooligosaccharide, was obtained in an enzymatically highly active form. This glycosyltransferase appeared to be unusual in that it displays a broad acceptor specificity toward both alpha- and beta-galactosides, whether structurally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 40 publications
2
82
3
Order By: Relevance
“…Genetic studies on LOS biosynthesis in strain F62 identified a gene cluster lgtA-E (10) that was responsible for the addition of most of the sugars found on the ␣ chain. Biochemical and genetic analysis have confirmed the functions of each of these genes (3,24,38,40) and their involvement in the synthesis of the ␣ chain. Additional genes needed to synthesize the ␤ and ␥ chain have also been identified (1,18), and most of the biochemical properties of these gene products have been defined (41).…”
mentioning
confidence: 84%
“…Genetic studies on LOS biosynthesis in strain F62 identified a gene cluster lgtA-E (10) that was responsible for the addition of most of the sugars found on the ␣ chain. Biochemical and genetic analysis have confirmed the functions of each of these genes (3,24,38,40) and their involvement in the synthesis of the ␣ chain. Additional genes needed to synthesize the ␤ and ␥ chain have also been identified (1,18), and most of the biochemical properties of these gene products have been defined (41).…”
mentioning
confidence: 84%
“…Alternatively, GP-2 (0.04 mM) was sulfated for 18 h at 37°C using [ 35 S]PAPS (0.2 mM, 30300 cpm/nmol) (Sigma) and TPST-1 (0.7 nmol/h) in a total volume of 56 l. The conversion of GP-2 to 35 SO 3 -GSP-2 was Ͼ95%. GP-5 was sulfated in a similar fashion as GP-6 using [ Enzymatic Synthesis of GSP-6Ј-␤1,3-GlcNAcT-Extension of GP-2 was carried out using purified recombinant ␤1,3-GlcNAcT from Neisseria meningitidis IgtA (34). Acceptor GP-2 (0.1 mM) was incubated for 20 h at 25°C in the presence of 1 mM UDP-GlcNAc and 8 nmol/h of ␤1,3-GlcNAcT (activity assayed using lactose as an acceptor) in a total volume of 100 l in 100 mM sodium cacodylate, pH 7.5, containing 5 mM ATP, 15 mM MnCl 2 , and 0.5% bovine serum albumin.…”
Section: Fig 2 Synthesis Of Glycosulfopeptide-6 (Gsp-6)mentioning
confidence: 99%
“…It was synthesized by a series of steps as outlined under "Experimental Procedures." A key step in the synthesis of GSP-6Ј is the addition of GlcNAc in ␤1-3 linkage to the Gal residue in the core 1 O-glycan by a recombinant ␤1,3-GlcNAcT from N. meningitidis IgtA (34). This glycopeptide, designated GP-3Ј, was subsequently modified by the action of ␤1,4-GalT, ␣2,3-sialylT, and ␣1,3-FucT to generate a glycopeptide designated GP-6Ј, which has sLe x on the extended core 1 O-glycan.…”
Section: Synthesis Of Glyco(sulfo)peptides-mentioning
confidence: 99%
“…These modifications contributed to a marked increase in extracellular ␤3GnT2 production from 0.017 [1] to 0.86 mU/ml. Moreover, ␤3GnT2 fused to its N-terminal with GFP uv exhibited ␤3GnT activity, with its specific activity being approximately 50-fold higher than that of a recombinant N-acetylglucosaminyltransferase (LgtA) from Neisseria meningitides [21]. Although its activity and specific activity cannot be directly compared because of the use of different substrates, GFP fusion techniques and the BES have been found to be suitable for the production of human ␤3GnT2.…”
Section: Discussionmentioning
confidence: 99%